METODOLOGI PENETAPAN KAIDAH KESAHIHAN HADIS (STUDI KOMPARATIF PEMIKIRAN M. SYUHUDI ISMAIL DAN MUHAMMAD AL-GHAZALI) - Sulidar Sulidar; Siti Ismahani; Tartila Yazofa (UIN Sumatera Utara Medan, 2022)
To research the Hadith a reference is needed. The reference used is the rule of Hadith validity. Research on Hadith needs to be done by examining the sanad, matan, and the narrators of the Hadith so that it can be seen the determination of the rules of the validity of the Hadith, because a Hadith is categorized as authentic if it fulfills the provisions or rules for the validity of the sanad and the matan of the Hadith. The method used in this research is literature, namely the data collected is first compiled, explained and then analyzed in depth, so that the answers to problems related to the subject matter are clear. The focus of the discussion in this study discusses the methodology for determining the validity of Hadith rules offered by M. Syuhudi Ismail and Muhammad Al-Ghazali, to find similarities and differences as well as methods from the theory of the validity of the Hadith used by the two figures. From the results of the study it was concluded that the two figures were closely related, which M. Syuhudi Ismail perfected the rules of authenticity of the Hadith sanad offered by Muhammad Al-Ghazali from the quality of the narrators and the way the narration was carried out in an element of the Hadith sanad, while Muhammad Al-Ghazali strengthened the criticism of the matan by testing the Alquran as the main reference in determining the quality of the rules of validity of the matan Hadith.